Exploration of Character Values in the Islamic Religious Education Curriculum (An Educational Perspective) - Sapruddin Sapruddin (International Journal of Religion, Humanity and Cultural Heritage, 2025)
This study aims to explore the character values contained in the Islamic Religious Education (PAI) curriculum and their role in student character building. Using a qualitative approach with a case study method, the research was conducted in several secondary schools in Indonesia. Data were collected through in-depth interviews with PAI teachers, students, and Islamic religious education experts, as well as classroom observations and curriculum documentation studies. The results showed that the PAI curriculum has integrated various character values, such as honesty, discipline, responsibility, empathy, and tolerance in the teaching materials. However, the implementation of this curriculum still faces challenges, including time constraints, lack of training for teachers in teaching character, and the negative influence of technology and social media on students. As a solution, this study suggests increased teacher training, integration of character values in all subjects, and positive use of technology in learning. This research provides important insights for the development of PAI curriculum as an effective tool in shaping students' character in the modern era.